2013
DOI: 10.1016/j.jacc.2013.03.051
|View full text |Cite
|
Sign up to set email alerts
|

Same-Day Discharge After Percutaneous Coronary Intervention

Abstract: In selected patients undergoing largely elective PCI, same-day discharge was associated with a low rate of major complications and appeared to be as safe as routine overnight observation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(38 citation statements)
references
References 64 publications
1
37
0
Order By: Relevance
“…Our study builds on and extends an accumulating body of evidence showing that SDD is safe and associated with lower costs of care. Two recent meta‐analyses of randomized controlled trials of SDD have confirmed the safety of SDD in terms of adverse events, such as mortality, myocardial infarction, major bleeding, blood transfusion, repeated revascularization, and rehospitalization; these adverse events were not significantly different between SDD and overnight stay groups, up to 30 days after PCI 3, 32. In the current climate of healthcare reform, lower costs of care offer a tremendous competitive advantage to hospitals.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Our study builds on and extends an accumulating body of evidence showing that SDD is safe and associated with lower costs of care. Two recent meta‐analyses of randomized controlled trials of SDD have confirmed the safety of SDD in terms of adverse events, such as mortality, myocardial infarction, major bleeding, blood transfusion, repeated revascularization, and rehospitalization; these adverse events were not significantly different between SDD and overnight stay groups, up to 30 days after PCI 3, 32. In the current climate of healthcare reform, lower costs of care offer a tremendous competitive advantage to hospitals.…”
Section: Discussionmentioning
confidence: 95%
“…However, what defines “carefully selected” elective PCI patients has been inconsistently applied, if defined at all 2, 3, 4, 5, 6, 7, 8, 9. Some studies have cautiously explored the feasibility of SDD beyond the low‐risk population,7, 10, 11, 12, 13, 14 but they were evaluated in selected patients or required protocols or checklists.…”
mentioning
confidence: 99%
“…Brayton et al [17] also showed that in selected patients undergoing PCI, same day discharge was not associated with a higher rate of major adverse events and this strategy appeared to be as safe as the overnight following coronary angioplasty. They also showed that patients who were excluded from same day discharge following PCI had worse short and long term outcomes [18].…”
Section: Discussionmentioning
confidence: 99%
“…The risk of major complications is highest immediately after PCI; most ma jor complications occur during the first 6 hours after PCI and decline thereafter. [191][192][193] Despite the low likelihood of a serious event, vasovagal responses with symptom atic bradycardia can occur at the time of femoral sheath removal, so it is reasonable to consider continuous elec trocardiographic monitoring immediately after interven tion until femoral sheaths are removed. Ischemia moni toring may provide assurance that postprocedural chest discomfort is from stent manipulation, not angina.…”
Section: After Nonurgent Pci Without Complicationsmentioning
confidence: 99%